Evaluando el rol de los musgos como plantas nodriza en los páramos (2019)
We evaluated the importance of mosses as facilitator in the Paramo. This analysis sought to evaluate if mosses can modify the microclimate and provide physiological advantages to the plants growing associated to them with respect to those growing over bare ground. It was found that mosses increase the water content of the soil and probably provides nitrogen since plants associated to the moss has higher chlorophyll content, higher photosynthetic efficiency and are better at regulating metabolic processes, which means plants growing associated to the moss are healthier. Is of vital importance to understand the ecological processes that structure the paramo vegetation since it is this vegetation the one that give the paramo ecosystem the capability of condensing and retaining water, thus becoming an important source of fresh water.